Effects of Using Emergency Department Patient Triage Online Instruction on Knowledge and Accuracy in Patient Triage of Nurse - Jaikhomsuk, Poonsap; Wangsrikhun, Suparat; Sukonthasarn, Achara (Journal of The Royal Thai Army Nurses, 2023)
Patient triage is a tool for effective resource management in caring of emergency patients. Nurses must have triage knowledge and skills to properly sort emergency patients based on their severity. This quasi-experimental study aimed to examine effects of using an Emergency Department Patient Triage Online Instruction on knowledge and accuracy in patient triage of nurse. The adult learning theory was used as the conceptual framework. The participants were 23 registered nurses working in emergency departments, which were purposive sampling from the Royal Thai Army hospitals. The study was conducted between April 2019 to May 2020. The research instrument was the Emergency Department Patient Triage Online Instruction, including 6 content topics and the practice scenarios. Data collection was done using the Emergency Patient Triage Knowledge Test and the Emergency Patient Triage Accuracy Record Form. The Wilcoxon matched-pairs signed-rank test was used to compare the knowledge and triage accuracy before and after online learning. The findings showed that the participants’ knowledge scores were statistically significantly higher than the scores before studying (p <.001), and the triage accuracy scores were statistically significantly higher than the scores before studying (p <.001). These findings reveal that online instruction can improve nurses’ knowledge and skill in patient triage at the emergency department.